70 Estimation of pulmonary arterial pressures by tricuspid regurgitation: a comparison with invasive data. (8th December 2021) - Landra, Federico; Mandoli, Giulia Elena; Chiantini, Benedetta; Barilli, Maria; Merello, Giacomo; De Carli, Giuseppe; Sciaccaluga, Carlotta; Lisi, Matteo; Focardi, Marta; D'Ascenzi, Flavio; Fineschi, Massimo; Iadanza, Alessandro; et al.
Abstract: Aims: The evaluation of the haemodynamic of pulmonary circulation is essential in various pathological conditions. Right heart catheterization (RHC) is the gold standard for the measurement of pressures and resistances in this context. However, since indications for RHC are limited, a more accessible estimation method would be helpful. This study aimed to explore the reliability of an echocardiographic method based on tricuspid regurgitation (TR) to estimate mean, systolic and diastolic pulmonary arterial (PA) pressures in a cohort of patients with advanced heart failure considered for heart transplantation. Methods and results: All consecutive patients with advanced heart failure considered for heart transplantation from 2016 to 2021 that had already performed right heart catheterization (RHC) as part of the workup and with an available echocardiographic exam were included ( n  = 91). Mean PA pressure was obtained adding mean right ventricular-right atrial (RV-RA) gradient to mean RA pressure. Systolic PA pressure was obtained adding maximum RV-RA gradient to mean RA pressure. Diastolic PA pressure was derived from mean and systolic PA pressures. Results were compared with PA pressures by RHC. Median time between RHC and echocardiography was 0 months [interquartile range (IQR): 0–3.5]. Median age was 58 years (IQR: 52–61.5), most of the patients were men (83.5%). The absolute mean difference between mean, systolic and diastolic PA pressures by RHC and echocardiography was 0.46 ± 9.78 mmHg, 2.18 ± 12.92   mmHg and −2.30 ± 8.61 mmHg, respectively. PA pressures by echocardiography significantly correlated with PA pressures by RHC (mean PA pressure: r  = 0.460, P  < 0.001; systolic PA pressure: r  = 0.520, P  < 0.001; diastolic PA pressure: r  = 0.372, P  < 0.001). AUC for prediction of pulmonary hypertension, defined as mean PA > 25 mmHg, by mean PA pressure by echocardiography was 0.828 and a cut-off of 25.5 mmHg demonstrated a high specificity (sensibility 66.7%, specificity 93.2%). Conclusions: Estimation of pulmonary arterial pressures through an echocardiographic method mainly based on tricuspid regurgitation gradients is reliable and an estimated mean pulmonary arterial pressure >25.5 mmHg has a high specificity for predicting pulmonary hypertension.